Higher incidence of hypotension episodes in women during the sub-acute phase of ST elevation myocardial infarction and relationship to covariates. - Petr Kala; Tomas Novotny; Irena Andrsova; Klara Benesova; Maria Holicka; Jiri Jarkovsky; Katerina Hnatkova; Lumir Koc; Monika Mikolaskova; Tereza Novakova; Tomas Ondrus; Lenka Privarova; et al. (PLoS ONE)
Objective The introduction of primary percutaneous coronary intervention (PPCI) has modified the profile of ST elevation myocardial infarction (STEMI) patients. Occurrence and prognostic significance of hypotension episodes are not known in PPCI treated STEMI patients. It is also not known whether and/or how the hypotension episodes correlate with the degree of myocardial damage and whether there are any sex differences. Methods Data of 293 consecutive STEMI patients (189 males) treated by PPCI and without cardiogenic shock were analyzed. Blood pressure was measured noninvasively. A hypotensive episode was defined as a systolic blood pressure below 90 mmHg over a period of at least 30 minutes. Results A hypotensive episode was observed in 92 patients (31.4%). Female sex was the strongest independent predictor of hypotension episodes (p < 0.0001), while there was no relationship to electrocardiographic STEMI localization. Hypotensive patients had significantly higher levels of troponin T and brain natriuretic peptide; hypotensive episodes were particularly frequent in women with increased troponin T. Treatment with angiotensin-converting enzyme inhibitor (ACEI), angiotensin receptor blocker (ARB) and betablockers was less frequent in hypotensive patients. After a mean 20-month follow-up, all-cause mortality did not differ between hypotensive patients and others. However, mortality in hypotensive patients who did not tolerate ACEI/ARB therapy was significantly higher compared to other hypotensive patients (p = 0.016). Conclusion Hypotension episodes are not uncommon in the sub-acute phase of contemporarily treated STEMI patients with a striking difference between sexes-female sex was the strongest independent predictor of hypotension episodes. Hypotensive episodes may lead to a delay in pharmacotherapy which influences prognosis. Higher incidence of hypotension in women could at least partially explain the sex-related differences in the use of cardiovascular pharmacotherapy which was repeatedly observed in various studies.